Identifying Causal Relationships in Strategy Maps Using Anp and Dematel - Oddershede-Herrera, A; Palominos-Belmar, P; Quezada-Llanca, L (Elsevier Ltd, 2018)
This paper presents a method for identifying the causal relationships between strategic objectives in a strategy map of a Balanced Scorecard. The Analytic Network Process (ANP) is used to estimate the direct influence between strategic objectives, and the Decision Making Trial and Evaluation Laboratory (DEMATEL) is used to obtain a matrix containing the full influences (direct and indirect) between those factors. Finally, a criterion is used to select those relationships that are important enough to be considered in the Impact-relation map defined by DEMATEL. The literature shows some cases in which ANP and DEMATEL are combined to build a strategy map; however, they are used in a completely different way from how they are utilized in the method proposed in this paper. As an illustration, the method is applied in a manufacturing company. © 2018 Elsevier Ltd